Genes in Tumor Formation - Riede Isolde (Journal of Hematology and Oncology Research, 2019)
With the definition of four gene classes, all differences between tumor cells and normal cells can be explained. Proliferative mutations induce a shortcut, forcing the cell to divide. They allow replication without control, induce somatic pairing defects of chromosomes and genome instability. Intact Tumor Supressors or mutant Switch Functions can inhibit this process. Oncogene mutations optimize the growth of the cells.
Keywords: Oncogenes